Eles nunca vão nos calar: um debate sobre a violência contra a mulher nos contos de Conceição Evaristo - Paim, Luciane de Lima (2019)
It is understood that violence against women is a historical phenomenon, born of the relations of gender inequality, inequalities of class, race, and sexuality, which are connected to the interests of the patriarchal way of production. It is also understood that it is difficult to analyze gender relations without understanding them in their historical, economic and social context. When analyzed in the patriarchal order, it is necessary to perceive them within and from the inequalities of class, race, and sexuality, without hierarchizing them, since these are also structuring axes of the society and are tied to each other. In this sense, this dissertation aims to comparatively analyze two works by Conceição Evaristo: Insubmissas Lágrimas de Mulheres (2011) and Olhos D'água (2014), and to identify, from this analysis, violence against women that is inflicted on the characters presented by the author. Conceição Evaristo is an active participant in movements of valorization of the black culture in our country, the aforementioned author made her debut in the literature in 1990, when she began to publish her short stories and poems in the series Cadernos Negros. Owner of versatile writing, Evaristo cultivates poetry, fiction, and essay. In this way, her texts have been getting more and more readers, which is considered very positive, whereas, centuries ago, a black woman's books would never have been read. As for the analyzes, they will be divided by blocks and will encompass the various forms of violence that the female characters suffer throughout the narratives. In addition, this dissertation intends to problematize issues involving the relations between racism, violence against women and patriarchalism. Methodologically, excerpts from the narratives that reinforce what was mentioned by Beauvoir, Butler, Spivak, Bourdie, Scott, Freyre, Tiburi, among others, on violence against women, gender inequality, racial discrimination, and patriarchalism. In addition, each literary work had the stories selected and divided into physical, sexual, patrimonial and symbolic violence. In the final stages, it can be concluded that of the short stories analyzed, all have some form of violence against women. As in this research, the woman is seen as a victim, therefore it is stated that of the characters presented by the author and selected for the study, all suffer some kind of violence, be it physical, symbolic, sexual, patrimonial or even all together.